2019
DOI: 10.19184/geosi.v4i3.13921
|View full text |Cite
|
Sign up to set email alerts
|

Urban Expansion Analysis and Land Use Changes in Rangpur City Corporation Area, Bangladesh, using Remote Sensing (RS) and Geographic Information System (GIS) Techniques

Abstract: This study aim  to attempt mapping out the Land Use or Land Cover (LULC) status of Regional Project Coordination Committee (RPCC) between 2009-2019 with a view of detecting the land consumption rate and the changes that has taken place using RS and GIS techniques; serving as a precursor to the further study on urban induced variations or change in weather pattern of the cityn Rangpur City Corporation(RCC) is the main administrative functional area for both of Rangpur City and Rangpur division  and experiencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…With the industrial and economic development, urbanization expanded rapidly. In 2009 the build-up area was 10.73% and in 2019 is 28.26% of the total area of Rangpur city [4].…”
Section: Introductionmentioning
confidence: 96%
“…With the industrial and economic development, urbanization expanded rapidly. In 2009 the build-up area was 10.73% and in 2019 is 28.26% of the total area of Rangpur city [4].…”
Section: Introductionmentioning
confidence: 96%
“…The number was 73,698 ha in 2009, and 50,924 ha in 2006. In another study, Rahman et al [11], using satellite images, showed that over the years the waterlogged area had increased from 865 ha in 1999 to 19,467 ha in 2008, making it a regular phenomenon for the hundreds of villages adjacent to the Kopadak river in Jessore and Satkhira districts. Hassan and Islam [12] detected the waterlogged area through Landsat imagery from 1972, 1989, and 2014 in Jessore district, where about 32,830 ha (13% of the total land) was identified as a waterlogged area.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that more than 650,000 people and around 128,000 ha of crop land (out of a total of 200,000 ha) were affected by monsoon flooding and subsequent waterlogging in these areas during 2011 [10]. Rahman et al [11] reported that about 101,800 people were affected by waterlogging in the Kopadak river basin of Jessore and Satkhira districts during 2003, and that this number increased to 845,000 people in 2008. Much variation can be seen in the number of affected people within the different districts and upazilas among the different reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Prabaharan et al, 2010); (Haladová and Petrovič, 2015), LULCC along with GIS and Remote Sensing data are employed in studies to detect changes that have occurred in a particular area over the years. The same method has been used by several other researchers such as (Santillan, Makinano and Paringit, 2010); (Haladová and Petrovič, 2015); (Khan et al, 2016); (Dami and Mayomi, 2016); (Abu Ghurah et al, 2018) and (Rahman, 2019), to quantify the extent of land use and land cover changes. Following this, the huge role of remote sensing and GIS in advancing research in land-use and land-cover change analysis cannot be downplayed.…”
Section: Introductionmentioning
confidence: 99%